Enrichment of LDPE-degrading bacterial consortia: Community succession and enhanced degradation efficiency through various pretreatment methods - Chanokporn Muangchinda; Onruthai Pinyakong (Scientific Reports)
Abstract Low-density polyethylene (LDPE) is a widely used plastic that significantly contributes to environmental pollution, and its biodegradation remains challenging. This study investigates the dynamics of bacterial communities in consortia enriched with LDPE as the sole carbon source. The potential for microbial diversity to adapt to polluted environments underscores its role in bioremediation. Community analysis identified Actinobacteria and Proteobacteria as key contributors to LDPE degradation, with dominant genera including Mycobacterium, Cupriavidus, Gordonia, Ochrobactrum, Nocardia, Agromyces, Amycolatopsis, and Cellulosimicrobium. The biodegradation of untreated and pretreated LDPE films was also examined, revealing that UV pretreatment significantly enhances degradation, with weight losses of 2.22–5.17% after 120 days. In contrast, sunlight and thermal treatments resulted in lower weight losses of 1.67–4.56% and 1.42–3.22%, respectively, while untreated LDPE showed only 1.32–2.80% weight loss. These findings underscore the importance of UV pretreatment in facilitating plastic biodegradation. Furthermore, potential LDPE-degrading Actinobacteria and Proteobacteria were isolated, identified as key players in the communities and co-occurrence networks, suggesting promising candidates for developing sustainable plastic waste management solutions. Moreover, this study is the first to reveal the potential LDPE degradation abilities of several genera, including Mesorhizobium, Agromyces, Amycolatopsis, Olivibacter, Aquamicrobium, Pseudaminobacter, and others.